Grafting after sinus lift with anorganic bovine bone alone compared with 50:50 anorganic bovine bone and autologous bone: results of a pilot randomised trial at one year. Issue 5 (May 2015) - Meloni, S.M.; Jovanovic, S.A.; Lolli, F.M.; Cassisa, C.; De Riu, G.; Pisano, M.; Lumbau, A.; Lugliè, P.F.; Tullio, A.
Abstract Our aim was to compare the outcome of implants inserted in maxillary sinuses augmented with anorganic bovine bone grafts compared with those augmented with mixed 50:50 bovine and autologous bone grafts. Twenty sinuses with 1–4 mm of residual crestal height below the maxillary sinuses were randomised into two groups according to a parallel group design (n = 10 in each). Sinuses were grafted using a lateral approach. In one group the grafts were 50:50 anorganic bovine bone and autologous bone and in the other anorganic bovine bone alone. After 7 months, 32 implants had been inserted. Outcome measures were survival of implants, complications, marginal changes in the height of the bone, and soft tissue variables (pocket probing depth and bleeding on probing). Probabilities of less than 0.05 were accepted as significant. No patient failed to complete the trial and no implant had failed at 1 year. There were some minor complications. After 12 months, the mean (SD) marginal bone loss (mm) was 1.06 (0.61) in the 50:50 group and 1.19 (0.53) in the anorganic bovine group. The mean (SD) values for pocket probing depth (mm) and bleeding on probing (score) were 2.49 (0.38) and 1.59 (0.82) in the 50:50 group and 2.31 (0.64) and 1.36 (0.87) in the anorganic bovine group (neither difference was significant). The present data are consistent with the hypothesis that the outcome of implants inserted in sinuses grafted with either material is comparable.